A comparative study of rafting mechanisms of Ni-based single crystal superalloys. (November 2020) - Long, Haibo; Bakhtiari, Sam R.; Liu, Yinong; Mao, Shengcheng; Wei, Hua; Chen, Yanhui; Li, Ang; Kong, Deli; Yan, Lu; Yang, Luyan; Zhang, Ze; Han, Xiaodong
Abstract: It is known that Ni-based superalloys experience microstructural rafting during high temperature straining. This paper presents a comparative study of the different rafting models by means of finite element modeling and experimentation investigation. It was found that uniaxial elastic loading does not alter the misfit or misfit isotropy of the structure, but causes repartitioning of the misfit into elastic strains in the γ and γ' phases. This causes an elastic strain energy anisotropy and hydrostatic stress anisotropy among the vertical and horizontal γ phase channels. Both anisotropies predict a raft structure that is contrary to the experimental observation. Through a carefully designed pre-treatment at 750 °C and under a uniaxial stress of 750 MPa, an anisotropic dislocation structure was created on the {001} γ'/γ interfaces without altering the cuboidal morphology of the γ' phase. This allows the evaluation of the influence of dislocations on the rafting behavior of the alloy. It was found that rafting occurred in the pre-treated samples containing anisotropic dislocation structures during thermal exposure without applied stress, instead of isotropic corsening, and that the raft structures conform to the expectations base don the anistropic dislocation strucutres. This demonstrates that an anisotropic dislocation structure on the {001} γ'/γ interfaces is a direct cause of rafting. This is attributted to the fact that dislocations on γ'/γ interfaces help to relax the local misfit strains, causing some to expand at the expense of others. At the same time, the formation of the anisotropic dislocation structure is a direct result of the anisotropy of elastic strains induced by the applied bia stess in during the pre-treatment. These explain the complex interplay of the elastic and plastic models reported the literature. Graphical abstract: Unlabelled Image Highlights: The elastic stretching alters the partitioning of elastic strains in two phases, whereas the misfit remains unchanged. The elastic strain energy and hydrostatic stress anisotropies are ruled out to be responsible for rafting. The anisotropic dislocation on γ'/γ interfaces wtith γ' phase cuboid morphology unchanged were created by pre-straining. The dislocation anisotropy is effective in causing rafting in Ni-based superalloys by causing misfit anisotropy.